Empirical Research on Value-at-Risk Computing Approaches in Evaluation of Financial Risks - LI, KAI (2012)
The aim of this dissertation is is to investigate how VAR computing approaches are implemented in evaluation of financial risk. Furthermore, objectives related to various aspects are investigated specifically. The first objective is to investigate how the three traditional VAR computing approaches and implement comparative analysis. The second objective is to investigate how failure frequency test is implemented in evaluating effectiveness of VAR results. The third objective is to investigate how VAR is computed in portfolio which contains either same financial instruments or different types of financial instruments. The fourth objective is to investigate how GARCH model is implemented in computing VAR of time series of financial returns.